Book Review Essay: Looking at Both Sides—Jack Welch in ReviewJack: Straight from the Gut, by WelchJack with ByrneJohn A.. New York: Warner Books, 2001.At Any Cost: Jack Welch, General Electric, and the Pursuit of Profit, by O'BoyleThomas F.. New York: Knopf, 1998. - Litz, Reg (Academy of Management Review, 2003)
The article presents reviews of the book ?Jack: Straight from the Gut,? by Jack Welch and John A. Byrne.